Prenatal screening - Ferreira, Manuel (2003)
Introduction: Introduction in Portugal of prenatal screening methods for chromossomic anomalies brought about doubts on its adequate use. Prenatal diagnostic protocols applied to pregnancies considered to be high-risk according to the usual standards (maternal age/family history) do not detect the about 80% of newborns with 21 trisomy who are born to mothers less than 35 years old, neither the 95% with neural tube defects who are the first family case. Screening tests identify higher-risk groups, who have a recommendation for additional testing. Objectives: To perform a review on prenatal screening methods available, its features and practical use. Methods: A literature search was performed, through the consultation of textbooks, internet pages of medical societies and associations which are references in the areas of obstetrics and family practice, as well as a Medline search between years 1995 and 2002, using as key words pre-natal diagnosis and screening test. Review: Screening can be performed in the first trimester of pregnancy using multiple biochemical markers and nuchal translucence echography. This allows for the calculation of specific risk for the occurrence of trisomies 21 or 18; the detection rate is close to 85% of cases. Second trimester screening also uses multiple biochemical markers plus echography. It can identify about 76% of trisomy 21 pregnancies and about 80% of neural tube defect situations. Both present a false-positive rate of about 5%. Integrated screening (first and second trimesters) allows for a higher detection rate. A positive screening result is an indication for a diagnostic test. A normal result does not excludes disease. There is no consensus about the screening of pregnant women of and over 35 years old. Conclusion: The doctor should inform the women on the existing options, its meaning and impact, allowing for an informed decision.